2012
DOI: 10.4067/s0717-97072012000400024
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Liquid Chromatographic Method for Naproxen and Esomeprazole in Binary Combination

Abstract: The present study reports the development and validation of a simple, economic and sensitive HPLC method for the concurrent determination of naproxen and esomeprazole in pharmaceutical formulations. Isocratic chromatography was performed with C-18 column and mixture of phosphate buffer (pH 6.1) and acetonitrile in ratio of (40:60, v/v) at 1.5 mlmin -1. The eluents were monitored at 302 nm using UV detector. The method was isocratic in the range of 9.38 to 300 µgml -1 for naproxen and 0.5 to 16 µgml -1 for esom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Reviewing the literature resulted in the occurrence of few methods for this FDC [22][23], however no stability indicating HPLC method was found for this FDC. We are involved recently to conduct research relating to method development of FDC of different drugs with varying chemical properties and many of these papers have been reported in the literature [24][25][26][27][28][29][30][31][32][33][34][35][36]. In order to fill this knowledge gap, it was attempted to develop and validate HPLC method with stability indicating properties for this FDC (ciprofloxacin and dexamethasone) not only in commercial formulations but also in human serum and urine.…”
Section: Preparation Of Human Urine Samplesmentioning
confidence: 99%
“…Reviewing the literature resulted in the occurrence of few methods for this FDC [22][23], however no stability indicating HPLC method was found for this FDC. We are involved recently to conduct research relating to method development of FDC of different drugs with varying chemical properties and many of these papers have been reported in the literature [24][25][26][27][28][29][30][31][32][33][34][35][36]. In order to fill this knowledge gap, it was attempted to develop and validate HPLC method with stability indicating properties for this FDC (ciprofloxacin and dexamethasone) not only in commercial formulations but also in human serum and urine.…”
Section: Preparation Of Human Urine Samplesmentioning
confidence: 99%
“…RP-HPLC and UV methods have been widely used for estimation of drug in bulk and dosage forms (Prasanthi et al 2011;Shukla et al 2011;Basaveswara Rao et al 2012;Singh et al 2012;Banerjee and Vasava, 2013;Singh and Dahiya, 2014). Literature review also revealed that simultaneous analysis of naproxen and esomeprazole has been carried out by UVSpectrophotometer (Mahaparale et al 2013;Patel et al 2012;, RP-HPLC (Jain et al 2011;Deshpande et al 2014;Ampati et al 2014;Saravanan et al 2014;Razzaq et al 2012), stability indicating simultaneous estimation of naproxen and esomeprazole by RP-HPLC (Reddy et al 2011), LC-MS/MS (Gopinath et al 2013) and UPLC method (Rao et al 2013;Bhavyasri et al 2013). The present work describes simple, specific, rapid, accurate and precise chromatographic method based on RP-HPLC mechanism for estimation of drugs in tablet dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts were therefore made to develop a novel, fast and validated stability indicating HPLC procedure for determining simultaneously both the drugs in pharmaceutical dosage forms and human serum. Currently we are developing analytical methods for drugs in binary combinations [16][17][18][19][20][21][22][23][24] and this study is a continuation of the previous work as it contained two active ingredients in formulation.…”
Section: Introductionmentioning
confidence: 99%